Effectiveness of different vaccine platforms in reducing mortality and length of ICU stay in severe and critical cases of COVID‐19 in the Omicron variant era: A national cohort study in Iran. Issue 3 (1st March 2023) - Jamaati, Hamidreza; Karimi, Saeed; Ghorbani, Fariba; Panahi, Yunes; Hosseini‐Baharanchi, Fatemeh Sadat; Hajimoradi, Maryam; Malek, Rayka; Noorali, Sima; Mokhtari, Majid; Khoundabi, Batoul; Sadr, Makan; Mohamadnia, Abdolreza; et al.
Abstract: Various severe acute respiratory syndrome coronavirus 2 vaccines with different platforms have been administered worldwide; however, their effectiveness in critical cases of COVID‐19 has remained a concern. In this national cohort study, 24 016 intensive care unit (ICU) coronavirus disease‐2019 (COVID‐19) admissions were included from January to April 2022. The mortality and length of ICU stay were compared between the vaccinated and unvaccinated patients. A total of 9428 (39.25%) patients were unvaccinated, and 14 588 (60.75%) patients had received at least one dose of the vaccine. Compared with the unvaccinated, the first, second, and third doses of vaccine resulted in 8%, 20%, and 33% lower risk of ICU mortality in the adjusted model, with risk ratio (RR): 0.92, 95% confidence interval (CI): 0.84–1.001, RR: 0.80, 95% CI: 0.77–0.83, and RR: 0.67, 95% CI: 0.64–0.71, respectively. The mean survival time was significantly shorter in the unvaccinated versus the fully vaccinated patients (hazard ratio [HR]: 0.84, 95% CI: 0.80–0.88); p  < 0.001). All vaccine platforms successfully decreased the hazard of ICU death compared with the unvaccinated group. The duration of ICU stay was significantly shorter in the fully vaccinated than in unvaccinated group (MD, −0.62, 95% CI: −0.82 to −0.42;  p  < 0.001). Since COVID‐19 vaccination in all doses and platforms has been able to reduce the risk of mortality and length of ICU‐stay, universal vaccination is recommended based on vaccine availability.